PATRIMONIO EN CUBA: EL CASO DE LA HABANA VIEJA COMO SITIO ARQUEOLÓGICO - Domínguez, Lourdes S. (Dialogos, 2018)
Resumo. O presente artigo discute a arqueologia histórica no âmbito da preservação do sítio arqueológico de Havana Velha, destacando a sua contribuição para o estudo da história social da cidade. Abstract. Historical archeology within the context of the conservation of the Old Havana archeological site is investigated. Research highlights the contribution of the site for the study of the city’s social history.